A school-based resilience intervention to decrease tobacco, alcohol and marijuana use in high school students - Daly Justine; Hodder Rebecca K; Freund Megan; Bowman Jenny; Hazell Trevor; Wiggers John (BMC, 2011)
Abstract Background Despite schools theoretically being an ideal setting for accessing adolescents and preventing initiation of substance use, there is limited evidence of effective interventions in this setting. Resilience theory provides one approach to achieving such an outcome through improving adolescent mental well-being and resilience. A study was undertaken to examine the potential effectiveness of such an intervention approach in improving adolescent resilience and protective factor scores; and reducing the prevalence of adolescent tobacco, alcohol and marijuana use in three high schools. Methods A non-controlled before and after study was undertaken. Data regarding student resilience and protective factors, and measures of tobacco, alcohol and marijuana use were collected from grade 7 to 10 students at baseline (n = 1449) and one year following a three year intervention (n = 1205). Results Significantly higher resilience and protective factors scores, and significantly lower prevalence of substance use were evident at follow up. Conclusions The results suggest that the intervention has the potential to increase resilience and protective factors, and to decrease the use of tobacco, alcohol and marijuana by adolescents. Further more rigorous research is required to confirm this potential.